The Role of The Kaaba and Zamzam Water in Shaping The Civilisation of The Hijaz Society - Faiz Rahman Azis; Rini Juliawati; Faris Sauqi Syahid; Hasanah, Uswatun (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study examines the strategic role of the Kaaba and Zamzam water in shaping the socio-economic civilization of the Hijaz region from the pre-Islamic period to the Islamic era. Although the Hijaz region is geographically arid and barren, Mecca succeeded in developing into a significant spiritual and economic center. This study aims to analyze the functions of these two elements as economic instruments that drive trade, social interaction, and political authority. The method used is the historical method, which encompasses the heuristic stage, source criticism, interpretation, and historiography. The results of the study indicate that the tradition of pilgrimage to the Ka’bah gave rise to seasonal markets and global trade networks, while Zamzam water ensured the sustainability of settlements and supported caravan trade routes. In conclusion, the Ka’bah and Zamzam water constitute the primary foundations of Hijaz civilization, which transformed through the institutionalization of the Hajj during the Islamic era. The implications of these findings reveal a shift in the function of local infrastructure toward a global agglomeration economy, which has reinforced the diplomatic and cultural legitimacy of the Hijaz region to this day.